Investigating Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Surface and Air Contamination in an Acute Healthcare Setting During the Peak of the Coronavirus Disease 2019 (COVID-19) Pandemic in London. (8th July 2020) - Zhou, Jie; Otter, Jonathan A; Price, James R; Cimpeanu, Cristina; Meno Garcia, Danel; Kinross, James; Boshier, Piers R; Mason, Sam; Bolt, Frances; Holmes, Alison H; Barclay, Wendy S
Abstract: Background: We evaluated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) surface and air contamination during the coronavirus disease 2019 (COVID-19) pandemic in London. Methods: Prospective, cross-sectional, observational study in a multisite London hospital. Air and surface samples were collected from 7 clinical areas occupied by patients with COVID-19 and a public area of the hospital. Three or four 1.0-m3 air samples were collected in each area using an active air sampler. Surface samples were collected by swabbing items in the immediate vicinity of each air sample. SARS-CoV-2 was detected using reverse-transcription quantitative polymerase chain reaction (PCR) and viral culture; the limit of detection for culturing SARS-CoV-2 from surfaces was determined. Results: Viral RNA was detected on 114 of 218 (52.3%) surfaces and in 14 of 31 (38.7%) air samples, but no virus was cultured. Viral RNA was more likely to be found in areas immediately occupied by COVID-19 patients than in other areas (67 of 105 [63.8%] vs 29 of 64 [45.3%]; odds ratio, 0.5; 95% confidence interval, 0.2–0.9; P = .025, χ 2 test). The high PCR cycle threshold value for all samples (>30) indicated that the virus would not be culturable. Conclusions: Our findings of extensive viral RNA contamination of surfaces and air across a range of acute healthcare settings in the absence of cultured virus underlines the potential risk from environmental contamination in managing COVID-19 and the need for effective use of personal protective equipment, physical distancing, and hand/surface hygiene. Abstract : Surface and air contamination with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was evaluated. SARS-CoV-2 RNA was detected but no viable virus was recovered. This underlines the potential risk of environmental contamination and the need for effective Infection Prevention and Control practices.